Dzikr Relaxation to Decrease College Student's Anxiety and Increase Happiness - Pihasniwati, Pihasniwati; Setiyani Subardjo, Ratna Yunita; Apriliyani, Rika; Kurniadewi, Elisa (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aimed to determine the effectiveness of dhikr relaxation in reducing anxiety and increasing happiness in college students. The subjects were 16 students of UIN Sunan Kalijaga aged 19-23 years. There were 2 hypotheses in this research. This research method was conducted by using quasi-experimental with a pretest and posttest control group design. Data collection tools were the HARS scale (Hamilton Anxiety Rating Scale), the OHQ scale (The Oxford Happiness Questionnaire), and Nexus Biofeedback. The data analysis used the Mann-Whitney U Test. The results of the first study showed that there was a difference in the anxiety score between the control group and the experimental group that took part in dhikr relaxation therapy, where the experimental group's score was greater than the control group's score as evidenced by the sig. of 0.005 (p<0.05). The results of the second study showed that there was no difference in the happiness score between the control group and the experimental group that took part in dhikr relaxation therapy, where the experimental group's score was greater than the control group's score as evidenced by the sig value. of 0.161 (p>0.05). The results of the analysis using the Nexus Biofeedback tool showed the sig. 0.028 (p<0.05). It can be concluded that dhikr relaxation was effective in reducing anxiety as indicated by a decrease in respiration frequency using the Nexus Biofeedback tool. However, dhikr relaxation has not been effective in increasing students’ happiness.